Effect of Melatonin on the Outcome of Assisted Reproductive Technique Cycles in Women with Diminished Ovarian Reserve: A Double-Blinded Randomized Clinical Trial - Bahia Namavar Jahromi; Sara Sadeghi; Shohreh Alipour; Mohammad Ebrahim Parsanezhad; Shaghayegh Moradi Alamdarloo (Iranian Journal of Medical Sciences, 2017)
Diminished ovarian reserve (DOR) significantly decreases the success rate of the assisted reproductive technique (ART). In this study, we assessed the effect of melatonin on the ART outcomes in women with DOR. A double-blinded, randomized, clinical trial was performed on 80 women with DOR as a pilot study in Shiraz, between 2014 and 2015. DOR was defined as the presence of 2 of the following 3 criteria: 1) anti-Müllerian hormone ≤1, 2) folliclestimulating hormone ≥10, and 3) bilateral antral follicle count ≤6. The women received 3 mg/d melatonin or a placebo since the fifth day of one cycle prior to gonadotropin stimulation and continued the treatment up to the time of ovum pickup. The ART outcomes were compared between the groups using SPSS software. Finally, there were 32 women in the case and 34 in the placebo groups. The mean age and basal ovarian reserve test were the same between the groups. The serum estradiol level on the triggering day was significantly higher in the case group (P=0.005). The mean number of MII oocytes was higher in the case group, but the difference did not reach statistical significance. Number of the patients who had mature MII oocytes (P=0.014), top-quality embryos with grade 1 (P=0.049), and embryos with grades 1 and 2 (P=0.014) was higher among the women who received melatonin. However, the other ART outcomes were not different between the groups. The serum estradiol level was higher and more women with DOR had good-quality oocytes and embryos after receiving melatonin; however, no other outcome was different between the case and control groups. Trial Registration Number: IRCT2014041417264N1